Cambiemos la historia. Una creación hipertextual basada en las TIC - María Marco Martínez; Darío Bañón Olivares (Investigaciones Sobre Lectura)
The historical chronology shows a narrow intertextual link between literature and music, present in various cultural and artistic contexts. It is essential, therefore, employment and use of educational skills as the main approach to promoting reading habit among students. Through to ICT and the area of Arts Education can develop an active methodology where standards and focused on the understanding and the promotion of reading fiction in the area of Spanish Language and Literature contents are worked, thus promoting creativity and autonomy in students through meaningful learning that contributes to the development of the learners. The draft is based on a teaching experience of hypertext creation aimed at students in 5th year of Primary Education (2nd Tranche), where classical literature (folktales) merges with the ternary musical form (ABA), the point starting from a narrative and musical invention which is reflected in ICT tools through different program used for editing and mounting. This is intended also to demonstrate the similarity between the structure and organization which keep the literary and musical patterns.